Knowledge Does Not Fall Far from the Tree - A Case Study on the Diffusion of Solar Cells in Germany - Johannes Rode; Alexander Weber (European Regional Science Association (ERSA), 2011)
The purpose of this paper is to illuminate the geographical diffusion of photovoltaic installations in Germany quantitatively and to test if preexisting photovoltaic systems stimulate further installations nearby; thus we investigate to which extent knowledge flows depend on geographic proximity. We develop an econometric model, which is discrete in time and space, but the level of geographical agglomeration is adjustable in arbitrarily small steps. We find that the probability to install a photovoltaic system dependents on the geographic proximity to agents, who have previously installed a photovoltaic system. In conclusion, our results confirm that knowledge exchange attenuates with distance.
Keywords: 330